2022
DOI: 10.3390/geriatrics7050110
|View full text |Cite
|
Sign up to set email alerts
|

Understanding User Requirements for a Senior-Friendly Mobile Health Application

Abstract: The advancement of mobile technologies has motivated countries around the world to aim for smarter health management to support senior citizens. However, the use of mobile health applications (mHealth apps) among senior citizens appears to be low. Thus, drawing upon user expectations, the present study examined user requirements for a senior-friendly mHealth application. A total of 74 senior citizens were interviewed to explore the difficulties they encounter when using existing mobile apps. This study followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 58 publications
0
19
1
Order By: Relevance
“…Technological stress refers to the stress and tension individuals feel when facing new technology, which could potentially lead to resistance to and distrust of new technological advancements [34] and has been explored and validated in numerous studies. For instance, Wu et al (2016) revealed a correlation between technological stress and the perceived ease of use of new technology [35].…”
Section: G Technological Stressmentioning
confidence: 99%
“…Technological stress refers to the stress and tension individuals feel when facing new technology, which could potentially lead to resistance to and distrust of new technological advancements [34] and has been explored and validated in numerous studies. For instance, Wu et al (2016) revealed a correlation between technological stress and the perceived ease of use of new technology [35].…”
Section: G Technological Stressmentioning
confidence: 99%
“…Envisioning a multitude of forthcoming advancements, the continual development of technology and its myriad innovations stands out. In the context of mHealth applications, anticipations of improved cost efficiency [50] and enhanced user-friendliness [51] are on the horizon. As technological literacy grows and the ubiquity of devices facilitating access to these applications increases [52], the prospect of heightened reach and accessibility to the population becomes apparent.…”
Section: Future Considerationsmentioning
confidence: 99%
“…However, despite the variety of products and the benefit the older population may have from mobile health technologies, their adoption rate has been relatively low, and over 43% of people aged 70 years old and above quit using mobile health technology after only 14 days [ 29 ]. According to Tajudeen et al [ 30 ], this happens due to complicated features and menus as well as interface designs that do not take into consideration the older population. Therefore, the goal of the present paper is to determine how to design mobile health technologies for walking targeted at supporting the older adult walker.…”
Section: Introductionmentioning
confidence: 99%